Implementasi Kerjasama Indonesia dan Jepang dalam Kebijakan Green Industry - Sigid Widyantoro (JBIMA (Jurnal Bisnis dan Manajemen), 2017)
In recent years, industrialization has a vital role in developing the economic capability of a nation. In the past, the focus of industrial sector often ignores the environmental impacts. Meanwhile, nowadays, environmental considerations become one of the important points in developing country’s industrial sector. Therefore, in the recent decade, the concept of green industry comes to preserve the sustainability and economic values of the industry as well as conserving the environment. As one of the countries which have cooperation with Indonesia regarding green industrial policy, Japan already implemented some green industry projects in Indonesia. This research tries to describe the implementation of green industrial policy between Indonesia and Japan. The method used in this research is library research method by studying past and recent literature regarding the development of green industrial policy in Japan as well as in Indonesia, also by observing partnership scheme by two countries that tackling this issue. The result of the research indicates that there are various projects that already implemented between Japan and Indonesia by developing a partnership to advancing the knowledge and technology in industrial sector while preserving the environment. Meanwhile, in Indonesia, there are many industrial sectors which are not yet applying the concept of green industry in their activity.